2004
DOI: 10.1177/216507990405200604
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Roles and Functions of Occupational Health Nurses in Japan

Abstract: The purposes of this study were to obtain descriptive information about the job duties and tasks of Japanese occupational health nurses and to compare the roles and functions of occupational health nurses in the United States and Japan. A modified version of a job analysis survey developed by the American Board for Occupational Health Nurses was used to collect data. The findings indicated 62% of Japanese occupational health nurses perform direct care roles, approximately half perform educating or advising and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…However, there are also differences in OH nursing education between countries throughout the world. In countries, such as the USA, Japan and Finland, postgraduate education is necessary to be able to work as an OHN and they are required to update their education at specific intervals, In other less developed and developing countries, such as Thailand, Lebanon, South Africa, Korea and Turkey, OHN education has been developed at the most basic level (Aksayan 2003; Grainger & Mitchell 2003; Ishihara et al. 2004; June et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are also differences in OH nursing education between countries throughout the world. In countries, such as the USA, Japan and Finland, postgraduate education is necessary to be able to work as an OHN and they are required to update their education at specific intervals, In other less developed and developing countries, such as Thailand, Lebanon, South Africa, Korea and Turkey, OHN education has been developed at the most basic level (Aksayan 2003; Grainger & Mitchell 2003; Ishihara et al. 2004; June et al.…”
Section: Discussionmentioning
confidence: 99%
“…OH nursing could be considered quite advanced in some countries while it just developing in others. The WHO and ILO recommend that all OH nursing educational programmes should have similar characteristics throughout the world in order to standardize practice (Aksayan 2003; Ishihara et al. 2004; June et al.…”
Section: Occupational Health Nursing and Educationmentioning
confidence: 99%
“…The ethical review board of the School of Health Sciences in Tokai University approved this study (11)(12)(13)(14)(15)(16). Along with the questionnaire, OHNs were sent to provide written explanations of the study objectives and ethical considerations, such as voluntary cooperation with no penalty for not responding to a questionnaire, anonymous response, and guaranteed privacy.…”
Section: Ethical Considerationmentioning
confidence: 99%
“…Regardless of the existence of full-time occupational health physician, this study also demonstrated that responding full-time OHNs generally provided support consecutive to individuals with cancer and their workplaces. It seems to represent the OHN's own expertise, in which OHNs provide consecutive support from primary to tertiary prevention phases 14,16,21) .…”
Section: Roles Of Ohns For Balancing Cancer Treatment and Work In Wormentioning
confidence: 99%
See 1 more Smart Citation